Succession in subtidal macrofouling assemblages of a Patagonian harbour (Argentina, SW Atlantic) - Rico, Alicia E. (2012)
Subtidal fouling assemblages usually consist of short-lived organisms. Colonisation sequences on man-made structures may thus be greatly affected by the temporal and spatial variability of propagule supply. This study explores the influence of seasonality on succession in the macrofouling assemblage of a Patagonian harbour (Argentina, Southwest Atlantic). Replicated artificial substrata were suspended horizontally and sampled at quarterly intervals during 1 year. The influence of seasonality on 1-year-old assemblages was further analysed using additional sets of replicated panels submersed at different seasons and collected 1 year later. Upper surfaces were always dominated by ephemeral algae, while lower surfaces exhibited high coverage of filter-feeding invertebrates. Regardless of submersion length, species richness was significantly higher on lower than on upper surfaces. A significant interaction between orientation and submersion length was found for the Shannon diversity index, meaning that temporal changes in diversity depended on substratum orientation. On the lower surfaces, diversity reached a maximum after 9 months and then declined, mainly due to extensive dislodgment of two species of ascidians. On algal-dominated upper surfaces, differences in structure of annual assemblages were due to seasonal changes in the abundance of ephemeral algae. This study shows that constancy or variability of 1-year-old assemblages whose development began at different seasons depended greatly on the life history of the organisms that settled and managed to persist on both surfaces, which in turn depended on substratum orientation.